INFERENCES BETWEEN SMART FARMING AND SUSTAINABLE DEVELOPMENT OF AGRICULTURE - Andreea Ion, Raluca; Raluca Ladaru, Georgiana; Stoian, Mirela; Petre, Ionut Laurentiu; Popescu, George Cristian (Economics of Agriculture, 2026)
Agriculture faces significant challenges related to globalpopulation growth, climate change and pressure on naturalresources. In this paper, the positive impact of integratingdigitalization into farming practices to promote sustainabilityand efficiency in the agricultural sector is explored. Theresearch aims to highlight the importance of smart farmingin the sustainable development of agriculture. This analysiswill be carried out at the level of scientific studies conductedaccording to the Scopus database. The main results showthat the interest in exploring IoT and digitalization inagriculture has increased in the last ten years, mostlybecause adopting sustainable practices and regenerativetechnologies minimizes the environmental impact andpromotes biodiversity. The findings add knowledge tothe literature and contribute to a better understanding ofthe benefits of implementing digitalization in agriculture;as such, farmers make more informed decisions aboutfertilization, irrigation, and crop protection, while reducingresource use and environmental impact.